Ladybird Readers Beginner Level - Timmy Time - The Magic Show (ELT Graded Reader) - Pitts,Sorrel (c)
Ladybird Readers is an ELT graded reader series for children aged 3-11 learning English as a foreign or second language. The series includes traditional tales, popular characters, modern stories, and non-fiction. Beautifully illustrated and carefully written by language learning experts, the series combines the best of Ladybird content with the structured language progression that will help children develop their reading, writing, speaking, listening and critical thinking skills .